2015
DOI: 10.1007/s00170-015-6874-z
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural aspects in Al–Cu dissimilar joining by FSW

Abstract: Sound AA2024-T3–Cu10100 dissimilar joints were obtained by friction stir welding offsetting the tool probe towards the aluminum sheet and employing selected processing parameters. Joint microstructure was analyzed by means of conventional optic microscopy as well as scanning electron microscopy. The weld bead exhibited welding zones and some features typically encountered in similar FSW. The nugget zone consisted of a mixture of recrystallized aluminum matrix and deformed and twinned copper particles. Onion ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Friction stir welding (FSW) is a solid state welding technique employed for joining several similar as well as dissimilar materials pairs, generally considered difficult to weld using conventional welding techniques [1][2][3][4][5]. The main benefits provided by FSW over conventional fusion welding processes can be summarized in the reduction of porosity, of microstructure alteration and of process induced residual stresses and distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir welding (FSW) is a solid state welding technique employed for joining several similar as well as dissimilar materials pairs, generally considered difficult to weld using conventional welding techniques [1][2][3][4][5]. The main benefits provided by FSW over conventional fusion welding processes can be summarized in the reduction of porosity, of microstructure alteration and of process induced residual stresses and distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Ouyang et al 9 and Carlone et al 10 described that the chemical affinity of aluminium and copper can lead to the formation of intermetallic phases such as CuAl 2 , CuAl, Al 3 Cu 4 and Cu 9 Al 4 , whose effects can be deleterious, and Bisadi 8 concluded that the amount of intermetallic compounds formed in the stir zone increases with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reason of the work-piece configuration was not explained in detail [20]. According to the investigation of dissimilar FSW between Al and Cu alloys, the suitable configuration and even the amount of offset of the tool from the joint centerline were considered to play an important role in obtaining high joints properties [21][22][23]. More recently, Sun et al conducted the dissimilar spot FSW between the UFGed 1050Al and 6061-T6 aluminum alloys [24].…”
Section: Introductionmentioning
confidence: 99%